Solvents Effect on 4-Phenyl-5-(2-Thienyl)-2,4-Dihydro-3H-1,2,4-Triazol-3-Thion Molecule: Experimental And Theoretical Study - Koparır, Pelin; Temüz, M.mürşit; Yıldırım, Mehmet (Niyazi BULUT, 2023)
In this study 4-phenyl-5-(2-thienyl)-2, 4-dihydro-3H-1,2,4-triazol-3-thion was synthesized using experimental method and later characterized using spectroscopic methods. The titled molecule is then designed, optimized and charaterized with theoretical first principle method. The result compared and the titled molecule is solvated with polar and non-polar solvent to see the effect of their interaction and changes that occurs in the spectroscopic results.
Keywords: Mathematical Sciences; Matematik